Pengaruh Corporate Governance, Koneksi Politik dan Profitabilitas Terhadap Potensi Tax Avoidance (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2020)
This study aims to analyze and obtain empirical evidence of Corporate Governance, Political Connection and Profitability to Tax avoidance. Independent variabels are proxied by Corporate Governance, Political Connection and Profitability, the dependent variable is proxied by Tax avoidance and control variables are proxied by Firm Size and Firm Age. Â The sample used in this study is secondary data derivied from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. Sample were taken by purposive sampling method and met the sample selection criteria. The sample used was 48 companies. Data is processed with Eviews Version 9 software and using the Generalized Least Square (GLS) method. The results show that Political Connections do not have an influence on Tax Avoidance, Corporate Governance that is proxied by Audit Quality does not have an effect on Tax Avoidance, while Corporate Governance which is proxied by the Audit Committee and Independent Board of Commissioners has a positive effect on Tax Avoidance. Profitability has negative effect to Tax avoidance.